‘Roof and Wall’ Tax Rate Reform in Addis Ababa: The Legal Conundrum and Socio-economic Pitfalls - Zelalem Teferra (Mizan law review, 2025)
The recent “roof and wall tax” reform in Addis Ababa was mainly prompted by economic imperatives to generate adequate and stable fiscal revenue for the City Government. The effort, however, is not supported by in-depth and detailed assessment of the socio-economic conditions and the paying capacity of different segments of the society. The new tax increase was not guided by up-to-date and comprehensive legal framework grounded in public consultation and parliamentary debate. Instead, it has relied on outdated Derg period legislation – Proclamation No. 80/1976. Qualitative research approach was used to generate the necessary data. Besides review of relevant legal instruments, in-depth and key informant interviews were employed. Despite generating robust revenue for the City Government and unlocking its capacity to plan and execute development projects, the study result has shown that the abrupt tax hike has negatively impacted the well-being of the low-income segment of the society, particularly the house owner-occupants, people with fixed income and female-headed households, all of whom have borne the burden and brunt of soaring cost of living induced thereof. It has also implied potential negative impact on the construction of affordable houses by the low and middle income groups; and this indicates the need for targeted interventions including initiating tax relief programs, low interest rate loan services, and exemptions to minimize the burden. Drawing on the pitfalls of the high ‘Roof and Wall’ tax hike, this article shows the need to take into account the potential cost of imposing high property tax while adopting and implementing the upcoming Federal Property Tax Law.